Perceived authenticity, perceived novelty risk and experiential value perception to revisit heritage destination in Melaka and Penang / Zaharah Mohamed Rani - Mohamed Rani, Zaharah (2015)
For decades now, tourist revisit intention has been the subject of debate in the tourism discipline, and especially within marketing. Although the tourism industry is growing worldwide, the industry continues to experience unpredictability over revisit intentions. Heritage is one of the core tourism products which have the potential to appeal to tourists, since heritage attractions permit the tourist to explore and experience the priceless character of past and present. However, when compared to other tourism segments, studies of tourist revisit intention in the discipline of heritage tourism, and especially for the case of Malaysia, continue to be neglected. Thus, the present thesis serves as a bridge to fill the gap and remedy the inconsistent empirical findings, by investigating tourist perceptions in the context of heritage tourism. The theoretical framework of the present study includes three constructs of independent variables namely perceived authenticity (object-based and existential authenticity), perceived novelty risk, and experiential value perception (host-guest relationship and activity). Empirical assessment of the theoretical framework includes a survey of 510 tourists who visited heritage tourism destinations in Malaysia, specifically Melaka and Penang. The resulting data were analysed through a process of multivariate analysis namely Structural Equations Modelling (SEM) using Analysis of Moment Structures (AMOS) software. The findings of the present thesis enhance the understanding of heritage tourism revisit intention behaviour and heritage tourism itself in several ways. The present study revealed support for previous research that perceived authenticity as the main construct of tourist revisit intention. The results demonstrate that the tourist is influenced to some extent by the originality and authenticity of the heritage products offered at the heritage sites located at Melaka and Penang. Furthermore, as the focus of this thesis is solely the study of perceived novelty risk, the study contributes to enhancing the understanding of the effect of novelty risk with revisit intention. The results indicate insignificant effect between perceived novelty risk with revisit intention. There is a similarity with other empirical findings on risk, as most researchers agree that the intention to revisit is affected when the destination is risky. The results also contribute to the understanding of the effects of experiential value perceptions on revisit intention. The results show that experiential value can be considered an influential construct that contributes to the tourist intention to revisit. Both host-guest relationship and activity provided at the destinations lead to enhanced knowledge and greater understanding of other cultural and heritage products. The findings from the study reveal that satisfaction partially mediates the relationship of perceived authenticity and experiential value perception to revisit intention. The present study also contributes to the empirical evidence of the effect of tourist motivation on the relationship of satisfaction and revisit intention. The results reveal that the effect of satisfaction and revisit intention is moderated by tourist motivation. The findings of the present study contribute to the literature on tourist behavioural intention by furnishing new empirical evidence on the effect between perceived authenticity, perceived novelty risk, and experiential value perception. Nevertheless, with regards to practical implications, the findings from the present study may aid tourism-related organisations, providers, and marketers, in understanding tourist behaviour and intention, and also in terms of marketing and strategizing for heritage tourism.